2022
DOI: 10.3389/fneur.2022.1079737
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and elastography role in pre- and post-operative evaluation of median neuropathy in patients with carpal tunnel syndrome

Abstract: IntroductionCarpal tunnel syndrome (CTS) is a common compression neuropathy of the median nerve in the wrist. Early diagnosis of CTS is essential for selecting treatment options and assessing prognosis. The current diagnosis of CTS is based on the patient's clinical symptoms, signs, and an electromyography (EMG) test. However, they have some limitations. Recently, ultrasound has been adopted as an adjunct diagnostic tool for electromyography (EMG). Ultrasound is a non-invasive and cost-effective technique. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several studies have reported the meaning of elastography in diagnosing CTS. Wu et al investigated the value of both ultrasound and real-time shear wave elastography (SWE) in evaluating the median nerve with CTS and demonstrated that SWE was useful in assessing the median nerve both before and after the operation ( 41 ). Recently, some research studies indicated that in CTS patients, blood flow changes of the median nerve can help to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the meaning of elastography in diagnosing CTS. Wu et al investigated the value of both ultrasound and real-time shear wave elastography (SWE) in evaluating the median nerve with CTS and demonstrated that SWE was useful in assessing the median nerve both before and after the operation ( 41 ). Recently, some research studies indicated that in CTS patients, blood flow changes of the median nerve can help to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Conduction blockade in both nerves is probably rare, but reports of the use of electrodiagnostic examination (EDX) have been sparse [ 8 ]. Recently, shear wave elastography (SWE) has been shown to have valuable diagnostic charac-teristics in carpal tunnel syndrome (CTS) [ 9 ]. It enables quick and objective assessment of changes in the nerve, allowing for conclusions about their nature [ 8 ].…”
Section: Introductionmentioning
confidence: 99%